2021
DOI: 10.1111/gcb.15895
|View full text |Cite
|
Sign up to set email alerts
|

Marine and freshwater regime changes impact a community of migratory Pacific salmonids in decline

Abstract: Marine and freshwater ecosystems are increasingly at risk of large and cascading changes from multiple human activities (termed "regime shifts"), which can impact population productivity, resilience, and ecosystem structure. Pacific salmon exhibit persistent and large fluctuations in their population dynamics driven by combinations of intrinsic (e.g., density dependence) and extrinsic factors (e.g., ecosystem changes, species interactions). In recent years, many Pacific salmon have declined due to regime shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…| 5 COMMENTARY income, food security, and cultural value to communities in the region (Johnson et al, 2019;Marushka et al, 2021). If historic logging has strongly reduced salmonid productivity throughout the temperate rainforest, as Wilson et al (2021) found in their study area, then new approaches to forest management could potentially yield major gains toward recovering fish populations and fisheries. Recent initiatives aiming to end large-scale logging of old-growth forest (https://www.fs.usda.gov/detai l/r10/landm anage ment/ resou rce ma nagem ent/?cid=FSEPR D950023) and incorporate indigenous values into natural resource management decisions (https://www2.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…| 5 COMMENTARY income, food security, and cultural value to communities in the region (Johnson et al, 2019;Marushka et al, 2021). If historic logging has strongly reduced salmonid productivity throughout the temperate rainforest, as Wilson et al (2021) found in their study area, then new approaches to forest management could potentially yield major gains toward recovering fish populations and fisheries. Recent initiatives aiming to end large-scale logging of old-growth forest (https://www.fs.usda.gov/detai l/r10/landm anage ment/ resou rce ma nagem ent/?cid=FSEPR D950023) and incorporate indigenous values into natural resource management decisions (https://www2.…”
mentioning
confidence: 90%
“…Thus, omitting carryover effects in the present study was justifiable, although it may have resulted in conservative estimates of the effects of freshwater conditions. Despite this simplifying assumption, Wilson et al (2021) find roughly equal overall effects of freshwater and marine conditions on steelhead population productivity. The strongest freshwater correlate of smolt production was cumulative logging activity in the watershed, and the strongest correlates of marine survival included coastal seal predation, competition with other salmon in the North Pacific, and an index of ocean climate.…”
mentioning
confidence: 90%
See 3 more Smart Citations